Models Of The Methodology For Developing A Scientific Worldview In Preschool Children - Saparniyazova Aigul (Zien Journals, 2025)
The formation of a scientific worldview in preschool-aged children is one of the key aspects of early cognitive development. During the early years, children develop fundamental concepts about nature, society, and the laws of the environment, laying a solid foundation for future learning. This article examines the main models of methodology for forming a scientific worldview in preschoolers, their features, and their application in educational institutions. The study discusses inquiry-based learning, game-based education, and digital technology-assisted teaching methods. The analysis results indicate that visual, interactive, and experimental approaches provide effective results in introducing children to scientific concepts. Additionally, the article explores the role of digital technologies in preschool education, the effectiveness of educational processes, and strategies for developing a scientific worldview.
Keywords: scientific worldview; preschool education